High participation rate among 25 721 patients with broad age range in a hospital-based research project involving whole-genome sequencing – the Lausanne Institutional Biobank (Swiss Medical Weekly, 2017)
AIMS We aimed to evaluate the interest of adult inpatients and selected outpatients in engaging in a large, real-life, hospital-based, genomic medicine research project and in receiving clinically actionable incidental findings. METHODS Within the framework of the cross-sectional Institutional Biobank of Lausanne, Switzerland, a total of 25 721 patients of the CHUV University Hospital were systematically invited to grant researchers access to their biomedical data and to donate blood for future analyses, including whole-genome sequencing. Multivariable logistic regression analysis was used to identify personal factors, including age, gender, religion, ethnicity, citizenship, education level and mode of admission, associated with willingness to participate in this genomic research project and with interest in receiving clinically actionable incidental findings. RESULTS The overall participation rate was 79% (20 343/25 721). Participation rate declined progressively with age, averaging 83%, 75%, 67% and 62% in patients aged